Quality Control Production Process Of Milk Pie Using Statistical Quality Control Analysis : Pengendalian Mutu Proses Produksi Pie Susu Dengan Analisis Statistical Quality Control - Adina Nur Halimah Sanwani; Ni Komang Ariasih; Putu Agus Arya Suta; Ruth Sani Manik; Ni Luh Putu Suciptawati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Product quality is an important factor in maintaining business competitiveness in the food industry, including milk pie products as a regional specialty souvenir. One milk pie producer at Bali is required to produce products with consistent quality in accordance with established standards. However, in the production process, several forms of product defects are still found that need to be controlled so as not to reduce quality and consumer satisfaction. This study aims to analyze quality control in the milk pie peroduction process using the Statistical Quality Control (SQC) method. The data used is production and product defect data obtained during a specific observation period. The analysis was carried out using several SQC tools, including check sheets and control charts, to identify the types of defects and assess the stability of the production process. Based on the observation results, the most dominant type of defect was broken milk pies. On December 12, 2025, the number of milk pies with broken defects was recorded at 32 units. The quality control analysis results showed that overall, the milk pie production process was stable and statistically controlled. The product defect rate was relatively low and still within acceptable control limits. This indicates that the quality control system implemented has been working quite well, although it is still necessary to.